Impact of Transformational Leadership on Coworker Support, Organizational Commitment, and Work-Life Balance: Enhancing Job Satisfaction and Reducing Emotional Exhaustion Among Employees of Major Retail Companies in Bangkok, Thailand - Somsanguan, Singharach; Rucktum, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study investigated the impact of transformational leadership on coworker support, work-life balance, and organizational commitment, thus enhancing job satisfaction and reducing emotional exhaustion among employees in major retail companies of Bangkok, Thailand. The proposed model was based on the theoretical evidence of social exchange theory (SET) and the social identity theory (SIT). The SET posits that when one person receives a favor from another, he tends to reciprocate it to the other person. Social identity theory (SIT) theory, on the other hand, proposes that when a person identifies himself as a member of the organization, he will be more committed to the organization’s goal. A self-administered questionnaire was distributed among 433 employees in major retail companies in Bangkok. Multiple Linear Regression analyses were used to test the hypotheses for analysis. Findings revealed that transformational leadership has a significant influence on increasing work-life balance, coworker support, and organizational commitment among employees while coworker support and work-life balance significantly increase organizational commitment. Coworker support was also found to reduce emotional exhaustion. Finally, organizational commitment causes a significant increase in job satisfaction and reduces emotional exhaustion.